Recombinant Variants of Tissue-type Plasminogen Activator Containing Amino Acid Substitutions in the Fibronectin Finger-like Domain and the Kringle 1 Domain - Yahara, Hitoshi; Matsumoto, Keiji; Maruyama, Hiroyuki; Nagaoka, Tetsuya; Ikenaka, Yasuhiro; Yajima, Kazuyoshi; Fukao, Hideharu; Ueshima, Shigeru; Matsuo, Osamu (Thrombosis and Haemostasis, 1994)
Tissue-type plasminogen activator (t-PA) is a fibrin-specific agent which is used to treat acute myocardial infarction. Pharmacokinetic-ally, t-PA is characterized by a rapid clearance from the circulation. In a previous study, we constructed variant forms of t-PA with genetic modifications at the fibronectin finger-like domain (finger domain) or at the kringle 1 domain (K1 domain). The finger modified variant, t-PA N37S.S38V.G39V.R40E. A41F.Q42S had about a 6.0-fold higher plasma half-life in vivo than wild-type t-PA. Two variants with modifications in the K1 domain, t-PA G161R.K162R.S165W and t-PA N115P, showed an improved kinetic parameters and a 2.2-fold higher plasma half-life in vivo than wild-type t-PA, respectively. To create a recombinant variant of t-PA with a higher enzymatic activity and a further prolonged half-life in vivo, the genes containing each modifications were joined and expressed in animal cells. The two variants, t-PA N37S.S38V G39V.R40E.A41F.Q42S.G161R.K162R.S165W and t-PA N37S.S38V.G39V.R40E.A41F.Q42S.N 115P, were purified from conditioned media and their biochemical, pharmacokinetic and thrombolytic profiles were investigated. Although the variant t-PA N37S.S38V.G39V.R40E.A41F.Q42S.G161R.K162R.S165W demonstrated an impaired enzymatic activity compared to the wild:type t-PA, the half-life of the variant, t-PA N37S.S38V.G39V.R40E.A41F.Q42S. N115P, following intravenous bolus injection in rabbits was considerably longer than that of finger-domain modified variants. Human plasma clot lysis assay estimated the fibrinolytic activity of both variants to be about 2.0-fold less effective than that of the wild-type t-PA. In the rabbit jugular vein clot lysis model, doses of 1.0 and 0.0625 mg/kg were required for about 70% lysis in the wild-type t-PA and t-PA N37S.S38V.G39V.R40E.A41F.Q42S.N115P, respectively. These findings suggested that the variant in this study can be used at a lower dosage in a single bolus injection.